1998
DOI: 10.1046/j.1471-4159.1998.70010335.x
|View full text |Cite
|
Sign up to set email alerts
|

Cyclin D2 Interacts with cdk‐5 and Modulates Cellular cdk‐5/p35 Activity

Abstract: Cyclin-dependent kinase-5 (cdk-5) is a serine! threonine kinase that displays neurone-specific activity. Experimental manipulation of cdk-5 expression in neurones has shown that cdk-5 is essential for proper development of the nervous system and, in particular, for outgrowth of neurites. Such observations suggest that cdk-5 activity must be tightly controlled during development of the nervous system. To identify possible regulators of cdk-5, we used the yeast two-hybrid system to search for proteins that inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
27
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 39 publications
1
27
0
Order By: Relevance
“…However, Guidato et al reported that cyclin D2 modulates the activity of the Cdk5-p35 complex, although the specific mechanism was not investigated in this study (Guidato et al, 1998). In agreement, a recent study revealed that cyclin D1 modulates Cdk5-p35 activity, possibly by competing with p35 binding to Cdk5 (Modi et al, 2012).…”
Section: Cyclin Dsupporting
confidence: 81%
“…However, Guidato et al reported that cyclin D2 modulates the activity of the Cdk5-p35 complex, although the specific mechanism was not investigated in this study (Guidato et al, 1998). In agreement, a recent study revealed that cyclin D1 modulates Cdk5-p35 activity, possibly by competing with p35 binding to Cdk5 (Modi et al, 2012).…”
Section: Cyclin Dsupporting
confidence: 81%
“…PAK1 activities in transfected CHO cells were assayed essentially as described previously by us for other kinases (21,22). Briefly, cells were co-transfected with PAK1, Rac, and ALS2, ALS2⌬DH, or vector encoding CAT as a negative control.…”
Section: Methodsmentioning
confidence: 99%
“…Other activators of Cdk5 include 2 neuronspeci c proteins, the P39 protein (Tang et al, 1995), and the vesicle trafficking-associated protein, Munc-18 (Shetty et al, 1995). Interestingly, cyclin-D and cyclin-E molecules, which regulate Cdk activity in proliferating cells, bind but do not activate Cdk5 (Guidato et al, 1998;Miyajima et al, 1995;Xiong et al, 1992).…”
Section: Dk5mentioning
confidence: 99%